An anti-inflammatory response of an organic food intervention by reducing pesticide exposures in children of Cyprus: A cluster-randomized crossover trial - Abimbola, Samuel Olushola; Konstantinou, Corina; Xeni, Christina; Charisiadis, Pantelis; Makris, Konstantinos C. (My University, 2024)
Organic food consumption in children has been shown to reduce the body burden of chemical pesticides. However, there is little evidence of human health benefits associated with the consumption of organic foods. The objectives were to i) determine the effectiveness of an organic food intervention treatment in reducing the magnitude of an inflammation biomarker (C-reactive protein, CRP) in children (10-12 years) and ii) assess the association between the urinary biomarkers of exposure to pesticides and CRP. This work was part of the ORGANIKO cluster-randomized cross-over trial entailing a 40-day organic food treatment in healthy children. Urinary biomarkers of exposure to pesticides and inflammation (CRP) were measured using tandem mass spectrometry and ELISA immunoassay, respectively. Linear mixed-effect regression models of CRP were used to account for the effect and duration of organic food treatment. Multiple comparisons were handled using Benjamini-Hochberg correction. Results supported an anti-inflammatory effect of organic food treatment in children, albeit with mixed results, depending on the creatinine adjustment method; biomarker levels were divided by urinary creatinine (method a1), or urinary creatinine was used as a fixed effect variable (a2). In the a1 method, a time-dependent reduction for creatinine-adjusted CRP (β = -0.019; 95% CI: -0.031, -0.006; q = 0.045) was observed during the organic food intervention period. A statistically significant association (β = 0.104; 95% CI: 0.035, 0.173; q = 0.045) was found between the biomarker of pyrethroids exposure (3-PBA) and CRP inflammatory biomarker, but not for 6-CN. In the a2 method, similar trend of time-dependent reduction for creatinine-adjusted CRP (β = -0.008; 95% CI: -0.021, 0.004; p = 0.197) was observed during the organic food intervention period, but did not reach statistical significance (q > 0.05); the associations of pyrethroid and neonicotinoid biomarkers with CRP were not statistically significant (q > 0.05). More studies are warranted to sufficiently understand the potential anti-inflammatory response of an organic food treatment.
Keywords: C-reactive protein (CRP); Inflammation; Organic food; Pesticides